Depression in Patients with Diabetes Mellitus: Prevalence & Factors Associated - Subedi, S.; Adhikari, A; Paudel, K.; Shrestha, L.; Sharma, N. (Journal of Psychiatrists’ Association of Nepal, 2020)
Introduction: Both diabetes and depression are major public health problems. Depression is a frequent comorbidity associated with diabetes. This study was aimed to find the prevalence of depression among patients with diabetes and to identify various factors associated with it. Material And Method: This is a cross-sectional study of diabetic patients visiting Internal medicine OPD of Universal College Of Medical Sciences, Bhairahawa, Nepal and referred for psychiatric evaluation. Sample size of 137 was included in 6 months period. Face to Face interview was conducted to gather socio-demographic and clinical profile of patients. Patient Health Questionnaire-9 was used to identify and classify depression. Frequency, Percentage, Chi-square test, Multivariate regression were applied. Results: The overall prevalence of depression was 27%. Depression was found to be significantly higher among female patients (p=0.009), patients suffering from diabetes mellitus for more than 15 years (p=0.054), patients under insulin therapy (p=0.034) and patients whose blood sugar level was uncontrolled(p=0.020) even with treatment. On regression analysis, treatment modality, blood sugar level, gender and treatment modality were found to be independent predictors of depression among diabetic patients. Patients on insulin therapy were four times more likely to have depression (OR=4.344, CI: 2.129 – 8.865, p<0.001). Female patients were two times more likely to have depression (OR=1.825, CI: 0.221 - 2.855, p<0.052). Conclusion: Almost one-fourth patients with diabetes also have depression. Factors like female sex, longer duration of diabetes, use of insulin therapy, uncontrolled diabetes increases the risk of developing depression in diabetic patients. Hence, routine screening of depression is necessary in patients with diabetes.